1993
DOI: 10.1007/bf00980684
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of linear furanocoumarins toSpodoptera exigua: Evidence for antagonistic interactions

Abstract: The linear furanocoumarins psoralen, bergapten, and xanthotoxin were tested for toxicity to the beet armywormSpodoptera exigua (Hübner) under short ultraviolet (UVB) radiation. Increased dietary concentrations of each furanocoumarin significantly decreased insect larval weight, extended generation time, and induced higher mortality. Xanthotoxin was the most toxic, followed by psoralen and bergapten. Combining psoralen with bergapten, xanthotoxin, or both resulted in significantly antagonistic effects on insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…In one case, this restriction was not met, leading them to identify one clearly non-synergistic interaction as synergistic (the combination effects of h-PT with ''Rs-2S3'' in Medium A on growth of the fungus A. brassicola in Table II of their paper). Diawara et al (1993) used a 2 analysis to test for antagonistic effects of chemical combinations on larval mortality. The expected mortality of a chemical combination was determined from the observed mortality of each compound as follows:…”
Section: Methods Used In the Ecological Literature For Detecting Intementioning
confidence: 99%
See 1 more Smart Citation
“…In one case, this restriction was not met, leading them to identify one clearly non-synergistic interaction as synergistic (the combination effects of h-PT with ''Rs-2S3'' in Medium A on growth of the fungus A. brassicola in Table II of their paper). Diawara et al (1993) used a 2 analysis to test for antagonistic effects of chemical combinations on larval mortality. The expected mortality of a chemical combination was determined from the observed mortality of each compound as follows:…”
Section: Methods Used In the Ecological Literature For Detecting Intementioning
confidence: 99%
“…We also mention one case of synergy from crop plants (Terras et al 1993). We know of only one case of antagonism in the ecological literature (Diawara et al 1993). We suggest the primary reason for this scarcity is the difficulty of detecting and analyzing interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, we know of very few studies that have reported antagonistic interactions (but see Diawara et al, 1993; Nelson and Kursar, 1999; Nuringtyas, 2014). Here, for all five tested PA free bases combined with CGA, significant antagonistic interactions were found on thrips mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the combination of two amides (Dyer et al, 2003; Richards et al, 2010; Whitehead and Bowers, 2014), the combination of two potato glycoalkaloids (Smith et al, 2001), the combination of two iridoid glycosides (Richards et al, 2012), the combination of two linear furanocoumarins (Diawara et al, 1993; Calcagno et al, 2002), the combination of PA free bases and PA N -oxides (Macel et al, 2005; Liu et al, 2017) on the performance of herbivores. Perhaps of greater importance is to study interacting effects between metabolites from different chemical classes on plant defense as the chemical properties of different metabolites might facilitate or counteract each other.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, bergapten has been found to occur in highest concentrations, followed by xanthotoxin, but psoralen is often observed only in trace quantities (Trumbe et al, 1990;Trumbe et al, 1992;Diawara et al, 1993). However, other studies have found that xanthotoxin (Beier et al, 1983) or psoralen (Diawara et al, 1993;Trumble et al, 1990) is most abundant (Stanley-Horn, 1999).…”
Section: Name Of Compoundmentioning
confidence: 99%